Contrast Enhancement of the Brain by Folate-Conjugated Gadolinium–Diethylenetriaminepentaacetic Acid–Human Serum Albumin Nanoparticles by Magnetic Resonance Imaging - Huedayi Korkusuz; Karsten Ulbrich; Verena Bihrer; Katerina Welzel; Valery Chernikov; Thomas Knobloch; Sabine Petersen; Frank Huebner; Hanns Ackermann; Svetlana Gelperina; Yuecel Korkusuz; Wolfgang Kromen; et al. (Molecular Imaging)
Different from regular small molecule contrast agents, nanoparticle-based contrast agents have a longer circulation time and can be modified with ligands to confer tissue-specific contrasting properties. We evaluated the tissue distribution of polymeric nanoparticles (NPs) prepared from human serum albumin (HSA), loaded with gadolinium–diethylenetriaminepentaacetic acid (Gd-DTPA) (Gd-HSA-NP), and coated with folic acid (FA) (Gd-HSA-NP-FA) in mice by magnetic resonance imaging (MRI). FA increases the affinity of the Gd-HSA-NP to FA receptor–expressing cells. Clinical 3 T MRI was used to evaluate the signal intensities in the different organs of mice injected with Gd-DTPA, Gd-HSA-NP, or Gd-HSA-NP-FA. Signal intensities were measured and standardized by calculating the signal to noise ratios. In general, the NP-based contrast agents provided stronger contrasting than Gd-DTPA. Gd-HSA-NP-FA provided a significant contrast enhancement (CE) in the brain ( p = .0032), whereas Gd-DTPA or Gd-HSA-NP did not. All studied MRI contrast agents showed significant CE in the blood, kidney, and liver ( p < .05). Gd-HSA-NP-FA elicited significantly higher CE in the blood than Gd-HSA-NP ( p = .0069); Gd-HSA-NP and Gd-HSA-NP-FA did not show CE in skeletal muscle and gallbladder; Gd-HSA-NP, but not Gd-HSA-NP-FA, showed CE in the cardiac muscle. Gd-HSA-NP-FA has potential as an MRI contrast agent in the brain.